Significance of Regional Planning in India Context: Promoting Economic Well-being through Regional Planning in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Regional Planning is actually an organized and deliberate practice of development of a region or maybe regions, which, in the course of its, brings out the improvement potentialities of each region, as well as, taking into account the limits of both material and human information within each region, suggests techniques for the development of theirs, so that the nation as an entire could achieve a better level of economic well-being. The primary goal behind regional planning is bringing about the improvement of the region in a planned and systematic fashion. Regional planning is even more driven by the fast overall improvement of the national economy.